Estudo da corrosão de ligas ferrosas em diesel e biodiesel - Matos, Larissa Aparecida Corrêa (2013)
Biodiesel is an renewable fuel, that can help reduce emissions of greenhouse gases to atmosphere. The biofuel, however, is prone to contamination by water, metals, microorganisms and other impurities that can change the initial properties of the fuel. The contact of damaged fuel with automotive systems and storage tanks can cause corrosion. Determination of corrosion by fuels and biofuels direct is difficulted by the conductivity necessary to use the conventional electrochemical method. Therefore, it is proposed to study the corrosion of metals exposed to fuel and biofuel by indirect method, by immersing the metal on the fuel for a period and then immerse it on a strong electrolyte to obtain the electrochemical parameter. Samples of carbon steel SAE 1010 and stainless steel AISI 304 were immersed in biodiesel and diesel samples in presence and absence of E. coli, at 30°C. Electrochemical measures were realized after 10 days of immersion. The results indicate that both carbon steel and stainless steels are damaged by the fuels and that the microorganism accelerates the corrosive process. The metal`s presence accelerates the auto-oxidation of biodiesel. For stainless steel, diesel was more corrosive than the varieties of biodiesel studied, while for carbon steel, biodiesel mixer was more corrosive than diesel. In microorganism presence, the varieties of biodiesel studied were more corrosive than mineral diesel.